Responses of Photosynthetic, Agronomic Traits, and Yields to Different Nitrogen Regimes in Juice Sugarcane cv. Suphanburi 50 in Low‐Fertility Soil - Nateetip Sawatraksa; Ruttanachira Ruttanaprasert; Chorkaew Aninbon; Preeyanuch Lakhunthod; Neeranuch Phiwdeang; Anon Janket (International Journal of Agronomy, 2026)
This study investigated the photosynthetic, agronomic traits, and yields responses to different nitrogen regimes of sugarcane cv. Suphanburi 50 and examined their relationship with cane yield. Field experiment was conducted during October 2022–October 2023. Four nitrogen regimes, namely, 46.9 (N base), 93.8 (N base + 46.9), 140.7 (N base + 93.8), and 203.2 (N base + 156.3) kg N/ha were studied using a randomized complete block design (RCBD) with four replications in low‐fertility soil. Chlorophyll fluorescence (Fv′/Fm′), net photosynthetic rate (Pn), stomatal conductance (gs), transpiration (E), intercellular CO 2 (Ci), transpiration efficiency (TE), and agronomic traits were measured at 4, 8, and 12 months after transplanting (MAT). Biomass, cane and juice yields as well as brix were measured at 12 MAT. Applying nitrogen fertilizer at 140.7 and 203.2 kg N/ha significantly increased Fv′/Fm′, Pn, gs, Ci, and TE at 4 and 8 MAT. Applying nitrogen at 203.2 kg N/ha tended to produce higher stalk numbers (6.05 stalks/stool), cane yield (106.3 t/ha), and juice yield (33,856 L/ha); however, these traits as well as brix were not statistically significant among nitrogen regimes. These enhancements were of 15.24%, 11.89%, and 5.82% for stalk numbers, cane yield, and juice yield, respectively, when compared with N base control. Correlation showed that Fv′/Fm′ ( r = 0.55 ∗ ) and E ( r = 0.49 ∗ ) positively correlated with cane yield at harvest. Several agronomic traits correlated with cane yield, including tiller number at 4 MAT ( r = 0.51 ∗ ), and cane height, stalk number, stalk diameter, and green leaves number ( r = 0.41 ∗ –0.60 ∗∗ ) at 8 and 12 MAT. This study provides new insights into the physiological and agronomic performance of a juice‐type sugarcane cultivar grown in acidic sandy soils, offering valuable information for optimizing nutrient management and breeding strategies in juice sugarcane production.
Keywords: Sugarcane Cultivation and Processing; Banana Cultivation and Research; Cocoa and Sweet Potato Agronomy